2014
DOI: 10.1089/scd.2013.0371
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Menstrual Blood Stem Cells to Treat Premature Ovarian Failure in Mouse Model

Abstract: The incidence of premature ovarian failure (POF), also known as ovarian insufficiency, has been increasing in recent years. Although some treatments are currently available, improved treatment strategies are urgently required. Many researchers have reported that human endometrial stem cells (HuMenSCs), which exhibit stem/progenitor cell properties in vitro repaired damaged cells in vivo. Thus, we aimed to determine whether HuMenSCs can serve as cell therapy tools and be used for the treatment of POF. After tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(164 citation statements)
references
References 23 publications
9
148
0
7
Order By: Relevance
“…Evidence has shown that hUCMSCs have unique advantages compared to BMSCs (22), which make them a promising source of cells for treatment. According to previous studies, stem cells to treat ovarian injury are primarily administered via intravenous injection (IV) or in situ ovarian micro injection (MI) (23)(24)(25)(26). However, very few studies have examined suitable forms of hUCMSC therapy to delay ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that hUCMSCs have unique advantages compared to BMSCs (22), which make them a promising source of cells for treatment. According to previous studies, stem cells to treat ovarian injury are primarily administered via intravenous injection (IV) or in situ ovarian micro injection (MI) (23)(24)(25)(26). However, very few studies have examined suitable forms of hUCMSC therapy to delay ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…Premature ovarian failure (POF) is a typical pathological disease of the reproductive system in aging females (1)(2)(3)(4)(5). Patients with POF are <40 years old and commonly have the features of amenorrhea, hypoestrogenism and high levels of gonadotrophin (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Las técnicas y fórmulas utilizadas están descritas en la bibliografía (20)(21)(22)(23)(24). Se tomaron entre 5 y 10 muestras de cada mezcla obtenida y se anotaron, según procediese, los valores correspondientes.…”
Section: Caracterización Del Biomaterialsunclassified
“…El concepto más valorado fue el ítem nº 4 "concepto de componente básico (células madre)" con una media de 4,63 puntos sobre un máximo de 5; lo que sin duda se debe a la importancia que, en el campo de la Ingeniería Tisular, tiene el concepto de célula madre como elemento inherente a esta ciencia y base esencial y fundamental de la misma (20)(21)(22). Por otro lado el ítem menor puntuado fue el nº 9 "concepto de biofabricación (bioimpresoras)" con una media de 3,13 sobre 5; ello se debe probablemente a su reciente aparición en el contexto de la ingeniería tisular y al poco conocimiento de dicho concepto por parte del alumnado, que considera el proceso de biofabricación menos relevante y más relacionado con aspectos tecnológicos que con aspectos propiamente biomédicos (23,24).…”
Section: Conceptos Umbrales En Ingeniería Tisularunclassified
See 1 more Smart Citation